2007
DOI: 10.1007/s00774-007-0768-6
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting long-term compliance of osteoporotic patients with bisphosphonate treatment and QOL assessment in actual practice: alendronate and risedronate

Abstract: The aim of our study was to examine compliance with a daily dose of 5 mg alendronate (ALN) and 2.5 mg risedronate (RDN) in actual practice, and to determine the causes of noncompliance through a questionnaire. In addition, we studied the quality of life (QOL) of patients through another disease-related questionnaire. The overall compliance rate remained at approximately 40% one year after the initial dose. The rates did not differ significantly between the ALN group (783 patients) and the RDN group (491 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(35 citation statements)
references
References 40 publications
1
34
0
Order By: Relevance
“…One limitation of the present study is the lack of data on the effect of risedronate on ADL, since assessment of physical activity would have allowed evaluation of the significance of improvement of ADL, since improvement of pain by risedronate (Kamatari et al, 2007) might increase activities of daily living (ADL), which then might contribute in part to improvement of FN BMD and markers for atherosclerosis .…”
Section: Discussionmentioning
confidence: 98%
“…One limitation of the present study is the lack of data on the effect of risedronate on ADL, since assessment of physical activity would have allowed evaluation of the significance of improvement of ADL, since improvement of pain by risedronate (Kamatari et al, 2007) might increase activities of daily living (ADL), which then might contribute in part to improvement of FN BMD and markers for atherosclerosis .…”
Section: Discussionmentioning
confidence: 98%
“…Weycker et al [20] found that those who were compliant 90% or more of the time showed significantly reduced fracture risk (OR = 0.70, 95% CI, 0.52-0.93) than did those with an MPR less than 30. In the long term, poor compliance will lead to increased health care costs, because adverse events such as fractures are more likely [21,22]. McCombs et al [23] has shown that a decrease in fracture rates leads to reduced physician services, hospitalization services, and outpatient care, all of which lead to reduced health care costs.…”
Section: Consequences Of Poor Compliance and Persistence With Osteopomentioning
confidence: 99%
“…15 Although this difference is attributed to the more advanced age of onset in males, the cause has not been fully elucidated. In a study by Kamatari et al, 16 which included 1274 patients with OP, it was reported that medication compliance in males was lower than in females; however, the cause of this noncompliance was not investigated in their study.…”
Section: Discussionmentioning
confidence: 99%